Nilai Ramadhan dan Pendidikan Kaum Tertindas (Mustadh’afin): Tinjauan Atas Ekonomi Islam - Rizqon Halal Syah Aji; Azis Muslim (ADALAH, 2020)
Abstract:Ramadan teaches social care. Momentum that is present this month (fasting) includes the teaching of humans about education. The message of transformative Islam in education is the meaning of Ramadan on the education of the oppressed (mustadh'afin). Education on the grounds of equality of knowledge rights and also in obtaining economic distribution rights. Ramadan teaches economic equality and balance so that the practice of liberation from the economic downturn of the people can be overcome. Islam offers muamalah (economic activism) through Islamic economics. The aim is to open up confinement over economic oppression and also be aware of the obligations of fellow human beings to be economically just. The practice of Islamic economics tries to dismantle the deterioration of the lower class economy with the concept of financial inclusion.Keywords: Ramadan, Education of The Oppressed, Mustadh'afin, Islamic EconomicsAbstrak:Ramadhan mengajarkan kepedulian sosial. Momentum yang hadir pada bulan ini (puasa) diantaranya adalah pengajaran atas manusia tentang pendidikan. Pesan Islam transformatif dalam pendidikan yang dimaksud adalah pemaknaan Ramadhan atas pendidikan kaum tertindas (mustadh’afin). Pendidikan atas nalar kesamaan hak pengetahuan dan juga dalam memperoleh hak distribusi ekonomi. Ramadhan mengajarkan kesamaan dan keseimbangan ekonomi sehingga praktik pembebasan atas keterpurukan ekonomi umat dapat di atasi. Islam menawarkan muamalah (aktivisme ekonomi) melalui ekonomi syariah. Tujuannya adalah membuka keterkungkungan atas ketertindasan ekonomi dan juga menyadarkan akan kewajiban sesama manusia untuk dapat bersikap adil secara ekonomi. Praktik ekonomi Islam mencoba membongkar keterpurukan ekonomi kelas bawah dengan konsep keuangan insklusif. Kata Kunci: Ramadhan, Pendidikan Kaum Terindas, Mustadh’afin, Ekonomi Islam